Rancang Bangun Sistem Pengontrol PH Air Minum dari Water Treatment Kapal Menggunakan Micro Controller ESP 32 - Nur Rizka Umami; Prihastono Prihastono; Ardhiana Puspitacandri (Globe: Publikasi Ilmu Teknik, Teknologi Kebumian, Ilmu Perkapalan, 2024)
In order for life to exist on Earth, water is required and is particularly important on ships. Concerns about water scarcity arise because water resources cannot always meet demand. pH has an impact on the quality of drinking water, with an ideal range between 6.5-8.5. Alkaline water with a pH of 8.8 has health benefits, including helping to lower stomach acid and improve body oxygenation. The pH of drinking water recommended by the EPA is between 6.5-8.5 to ensure safe consumption. pH is a measure of the acidity or basicity of water, on a scale of 0-14, where 7 is considered neutral. The research plans to make a drinking water pH control system using an ESP 32 microcontroller. This research aims to control also monitor the pH of drinking water efficiently using ESP 32 microcontroller. This research uses the Research and Development (R&D) method to design pH control in drinking water solutions. The phases of the research include using a pH sensor to detect pH values, using an ESP 32 microcontroller to control pH, and validating and improving the product model. Overall system testing in the design of a drinking water pH controller system from water treatment is an important stage to ensure successful integration between all components and desired functionality. This testing process includes several main stages, Hardware Integration Testing: All hardware is physically connected and integrated, including ESP32, relays, solenoid valves, and pH sensors. This test is taken to ensure that all components are properly installed and interact with each other correctly. Software Integration Testing: This type of testing verifies that all features and functions of the system function as intended by the software program responsible for it. This includes testing Wi-Fi connections, integration with the Blynk platform, and programming logic as an automatic water controller. Testing System Functionality: to ensure that the intended features can be run properly, the system is tested in various usage scenarios. This includes testing the water controller automatically. the designed system can function normally and adjust appropriately to the designed controller system. From the data obtained regarding the performance results of the system built, it was found that the pH controller system can be run automatically based on the water that has been set as the set point of the system created. The monitoring system with IoT is also able to run well. The time needed will be more to control the pH in the range of 6.5-8.5.